2017
DOI: 10.1080/21645515.2017.1264795
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of immunity 18–19 years after vaccination against hepatitis B in 2 cohorts of vaccinees primed as infants or as adolescents in Italy

Abstract: This study was aimed at assessing the anti-HBs persistence and immune memory 18-19 y after vaccination against hepatitis B in healthy individuals primed as infants or adolescents. We enrolled 405 teenagers (Group A) vaccinated as infants, and 409 young adults (Group B) vaccinated as adolescents. All vaccinees were tested for anti-HBs and anti-HBc antibodies; those found anti-HBc positive were further tested for HBsAg and HBV DNA. Eight individuals belonging to Group B were positive for anti-HBc alone, and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
3
13
1
Order By: Relevance
“…A series of studies reported a satisfactory anti-HBs seroconversion, which was approximately 84.0 and 98.0%, after a booster dose was achieved [7, 1216]. In our study, a dramatic increase in the anti-HBs antibody positive rate was measured.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…A series of studies reported a satisfactory anti-HBs seroconversion, which was approximately 84.0 and 98.0%, after a booster dose was achieved [7, 1216]. In our study, a dramatic increase in the anti-HBs antibody positive rate was measured.…”
Section: Discussionsupporting
confidence: 63%
“…Several studies have reported the persistence of anti-HBs levels after primary vaccination and found that protective anti-HBs antibodies were maintained up to 20 years in approximately 37–77% of vaccinees [710]. The persistence of anti-HBs is related to a variety of factors, including the mother’s carrying status, regimens and type of vaccine used, time interval between the first and last injection of primary vaccination, and anti-HBs antibody peak level after full course of primary immunization [1012].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the higher the antibody response after the primary vaccination cycle, the longer the persistence of an anti-HBs concentration above the 10 mIU/mL threshold [1]. The results arisen in this study reinforce the importance of age at vaccination, as highlighted by the statistical significance in the multivariate analysis (OR 0.2; 95% CI = 0.1-0.8).…”
Section: Discussionsupporting
confidence: 72%
“…Factors such as age at vaccination, vaccine dosage [1, 3] and host genetic factors [28] play a fundamental role in maintaining the anti-HBs concentration. Furthermore, the higher the antibody response after the primary vaccination cycle, the longer the persistence of an anti-HBs concentration above the 10 mIU/mL threshold [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation